(untitled) (CIPEEX, 2025)
Private International Law is a branch of law that studies the rules used to regulate private relationships involving more than one country. The main focus is resolving conflicts of laws across borders, that is, deciding which law should be applied in situations involving different countries. Furthermore, it helps determine which court has the authority to hear these cases and analyzes whether decisions made in other countries are recognized and valid here. To this end, the study typically relies on research into books, laws, and documents, addressing basic concepts, their historical origins, and how this area of ​​law has evolved to the present day. Factors such as nationality, place of residence, and the location of the property are fundamental when deciding which law should be applied. At the same time, basic principles such as national sovereignty, legal cooperation between nations, reciprocity, and the preservation of public order guide this choice in practice. This analysis shows that Private International Law plays a very important role in ensuring security and predictability in relationships that cross borders, covering areas such as international trade, contracts between countries, marriage, divorce, inheritance, and international adoptions. It follows that, with globalization and greater interdependence between countries, this branch of law becomes even more relevant. It is an essential tool for harmonizing different legal systems and ensuring that rights are effectively respected worldwide.